“Anak adalah Aset”: Meta Sintesis Nilai Anak pada Suku Lani dan Suku Aceh - Agung Dwi Laksono; Ratna Dwi Wulandari (Jurnal Kesehatan Reproduksi, 2019)
Abstract Background: If a child gives values that were considered positive or beneficial to parents, then parents will place high expectations on the child. The study was conducted to synthesize the value of children in the Aceh Tribe and the Lani Tribe. Objective: The research aim was to explore the value of children in the Lani and the Acehnese. Methods: Using the meta-synthesis method in two manuscripts resulting from health ethnographic research, namely "The Dilemma of the Family Planning Program" (Acehnese Tribe in East Aceh, Aceh) and "Portrait of Noken Child Care Patterns in Lani Culture" (Lani Tribe in Tolikara, Papua). Results: Economically the people of Aceh and Lani consider children to be investments. This applies to girls. Socially, the two tribes consider children to be a complement to a family's life and a source of happiness. In religion, the Acehnese consider the child to be the successor to the religion, multiplying children was an effort to multiply the people. While Lani people believe in Christian teachings that encourage them to spread on the surface of the earth, this was done by multiplying offspring. For Acehnese children were important. They consider that the Acehnese boy could be the pride of the family and also the successor to the offspring. While Lani people value girls more than boys. Conclusions: Both tribes still want a large number of children, between 4-7 children. Both tribes also still hold strong the value of children economically, children were assets. Key words: the value of children, meta-synthesis, meta-aggregation, ethnography research, Aceh tribe, Lani tribe Abstrak Latar Belakang: Apabila seorang anak memberikan nilai yang dianggap positif atau menguntungkan bagi orang tua, maka orang tua akan menaruh harapan yang tinggi terhadap anak. Suku Aceh dan Suku Lani merupakan kelompok rentan yang perlu mendapat perhatian. Tujuan: Tujuan penelitian untuk mengeksplorasi nilai anak pada Suku Lani dan Suku Aceh. Metode: Meta sintesis pada dua manuskrip hasil riset etnografi kesehatan, yaitu “Dilema Program Keluarga Berencana” (Suku Aceh di Aceh Timur, Aceh) dan “Potret Pola Asuh Anak Noken dalam Budaya Lani” (Suku Lani di Tolikara, Papua). Studi difokuskan pada nilai anak secara: ekonomi; sosial; agama; preferensi gender; dan preferensi jumlah anak. Hasil: Secara ekonomi masyarakat Aceh dan Lani menilai anak adalah investasi. Hal ini berlaku bagi anak perempuan. Secara sosial kedua suku menilai anak adalah pelengkap hidup sebuah keluarga dan sumber kebahagiaan. Secara agama orang Aceh menilai anak itu penerus agama, memperbanyak anak adalah upaya untuk memperbanyak umat. Sedang orang Lani meyakini ajaran kristiani yang menganjurkan mereka untuk menyebar di permukaan bumi yang dilakukan dengan cara memperbanyak keturunan. Bagi orang Aceh anak laki itu penting. Mereka menganggap bahwa anak laki Aceh dapat menjadi kebanggaan keluarga dan sekaligus penerus keturunan. Sedang orang Lani menilai lebih tinggi anak perempuan dibanding laki-laki. Kesimpulan: Kedua suku masih menginginkan jumlah anak yang banyak, antara 4-7 anak. Kedua suku juga masih memegang kuat nilai anak secara ekonomi, anak adalah aset. Kata kunci: nilai anak, meta sintesis, meta agregasi, riset etnografi, suku Aceh, suku Lani